Inhibition of sPLA2-IIA Prevents LPS-Induced Neuroinflammation by Suppressing ERK1/2-cPLA2α Pathway in Mice Cerebral Cortex - Xiang, Yanxiao; Chen, Lin; Liu, Huiqing; Liu, Xiaoqian; Wei, Xinbing; Sun, Baozhu; Wang, Tian; Zhang, Xiumei (PLOS ONE, 2013)
Neuroinflammation is involved in various central nervous system (CNS) disorders, including brain infections, ischemia, trauma, stroke, and degenerative CNS diseases. In the CNS inflammation, secretory phospholipase A2-IIA (sPLA2-IIA) acts as a mediator, resulting in the generation of the precursors of pro-inflammatory lipid mediators, such as prostaglandins (PGs) and leukotrienes (LTs). However, the role of sPLA2-IIA in neuroinflammation is more complicated and remains unclear yet. In the present study, we investigated the effect of sPLA2-IIA inhibition by specific inhibitor SC-215 on the inflammation in LPS-induced mice cerebral cortex and primary astrocytes. Our results showed that the inhibition of sPLA2-IIA alleviated the release of PGE2 by suppressing the activation of ERK1/2, cPLA2α, COX-2 and mPGES-1. These findings demonstrated that sPLA2-IIA showed the potential to regulate the neuroinflammation in vivo and in vitro, indicating that sPLA2-IIA might be a novel target for the treatment of acute neuroinflammation.